QTL Mapping of Adult Plant Resistance to Leaf Rust in the N. Strampelli × Huixianhong RIL Population - Man Li; Zhanhai Kang; Xue Li; Jiaqi Zhang; Teng Gao; Xing Li (Agronomy, 2025)
Leaf rust (LR) is a devastating foliar disease that impacts common wheat (Triticum aestivum L.) globally. For optimal disease protection, wheat cultivars should possess adult plant resistance (APR) to leaf rust. In the current study, the objective was to map quantitative trait loci (QTL) related to leaf rust resistance. This was achieved by using 193 recombinant inbred line (RIL) populations which were developed from the cross between N. Strampelli and Huixianhong. Four trials were conducted in China (three in Baoding, Hebei province, and one in Zhoukou, Henan province) to assesses the leaf rust response of the RILs and parental lines. The wheat 660K SNP array and additional SSR markers were used to genotype the RIL populations. Through inclusive composite interval mapping (ICIM), three QTL related to leaf rust (LR) resistance were detected. ICIM was also employed to reevaluate previously published data in order to identify QTL with pleiotropic effects. To determine the physical positions, the flanking sequences of all SNP probes were compared against the Chinese Spring wheat reference sequence through BLAST searches. Three leaf rust resistance loci, two on chromosome 2A and 5B, were contributed by N. Strampelli. QLr.hbau-2AL.1 was detected in three leaf rust environments with phenotypic variance explained (PVE of 12.2–17%); QLr.hbau-2AL.2 was detected in two environments with 12.5–13.2% of the PVE; and QLr.hbau-5BL was detected in all leaf rust environments with phenotypic variance explained (PVE) of 17.8–19.1%. QLr.hbau-5BL exhibited potentially pleiotropic responses to multiple diseases. The QTL and the associated flanking markers discovered in this study could prove valuable for purposes such as fine mapping, the exploration of candidate genes, and marker-assisted selection (MAS).